2013
DOI: 10.1021/jo302515c
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Quinazolin-4(3H)-ones via Amidine N-Arylation

Abstract: Pyrido[4,3-d]pyrimidin-4(3H)-one (1) was prepared by reacting 2-trifluoromethyl-4-iodo-nicotinic acid (2) with amidine 9a catalyzed by Pd(2)(dba)(3) and Xantphos, followed by cyclization effected with HBTU and subsequent demethylation using PhBCl(2). The amidine arylation method was found applicable for the syntheses of quinazolin-4(3H)-ones. Thus, reaction of 2-bromo or 2-iodo benzoate esters with amdidines afforded substituted quinazolin-4(3H)-ones in 44-89% yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 33 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…In addition, both alkenyl-and alkyl-substituted aldehydes were well compatible with the reaction conditions to generate the desired products 3m and 3n in moderate yields (entries [13][14]. Next, 2-bromobenzamides 1 with different substitution patterns were investigated under our optimized reaction conditions, and it was observed that the tandem reactions of amides 1b-d with different aldehydes 2 and aqueous ammonia proceeded smoothly to afford 2-substituted quinazolinones 3o-w in yields ranging from 30-79% (entries [15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both alkenyl-and alkyl-substituted aldehydes were well compatible with the reaction conditions to generate the desired products 3m and 3n in moderate yields (entries [13][14]. Next, 2-bromobenzamides 1 with different substitution patterns were investigated under our optimized reaction conditions, and it was observed that the tandem reactions of amides 1b-d with different aldehydes 2 and aqueous ammonia proceeded smoothly to afford 2-substituted quinazolinones 3o-w in yields ranging from 30-79% (entries [15][16][17][18][19][20][21][22][23].…”
Section: Resultsmentioning
confidence: 99%
“…Li and co-workers (Pfizer) developed a procedure for the large-scale synthesis of quinazolin-4(3 H )-ones. 373 Targeting quinazoline 436 ( Scheme 108 b), the research group initially examined a Cu-catalyzed approach to access intermediate 435 . However, they only observed low conversion to the desired product.…”
Section: Amides and Amide Derivativesmentioning
confidence: 99%
“…56 The route highlights the formation of a pyridopyrimidin-4(3H)-one using a palladium-catalyzed amidine N-arylation reaction. 56 The route highlights the formation of a pyridopyrimidin-4(3H)-one using a palladium-catalyzed amidine N-arylation reaction.…”
Section: General Heterocycle Synthesismentioning
confidence: 99%